Capacity Building for Raudhatul Athfal Teachers through the Development of Merdeka Curriculum Teaching Modules - Jhoni Warmansyah; Meliana Sari; Restu Yuningsih; Sherly Wiliany; Rahayu Yandira S Siregar; Zakiah Zalzabila (Journal of Comunity Service in Early Childhood Education, 2025)
Background: Raudhatul Athfal (RA) teachers often face challenges in developing effective teaching modules aligned with the Merdeka Curriculum due to limited training and difficulties in translating curriculum principles into classroom practice. Aims: This community service aims to strengthen RA teachers’ capacity in developing teaching modules based on the Merdeka Curriculum. Methods: This program employed a Participatory Action Research (PAR) approach through mentoring activities conducted offline over two days. The program involved 52 RA teachers in a series of activities including material delivery, hands-on module design, and reflective discussions. Data were collected through observations, interviews, focus group discussions (FGDs), and questionnaires. Result: The results indicate a significant improvement in teachers’ understanding and skills in developing teaching modules aligned with the Merdeka Curriculum. Teachers demonstrated better comprehension of curriculum structure, learning outcomes (CP), and the formulation of learning objectives (TP) and teaching modules (ATP). In addition, their ability to design structured and contextualized modules improved, particularly in aligning learning activities with student needs and integrating appropriate learning media. The evaluation results showed a high level of participant satisfaction, with an average score of 3.95 categorized as “Good,” indicating that the mentoring activities were well-received. Teachers also showed increased confidence in implementing the curriculum in classroom practice, including the use of technology. Furthermore, the participatory and hands-on approach enabled active engagement, leading to deeper understanding and improved practical skills. Conclusion: The mentoring program effectively enhanced RA teachers’ capacity in designing innovative and contextualized teaching modules aligned with the Merdeka Curriculum, making it a practical and replicable model for similar educational programs.